Carbono e emissão de CO2 em sistema silvipastoris e pastagem com aplicação de biofertilizante - Fonseca, Leandro Jamerson (2017)
Nowadays, pasture degradation is a widespread phenomenon throughout the Brazilian territory, although the proportion of affected area is regionally variable. For adressing this concern, the integration of forest and livestock, through silvopastoral systems, is an alternative that has been gaining space among producers. On the other hand, Brazil is one of the world's leading producers of pork meat, which generates massive amount of waste, such as swine wastewater. After passing through the biodigestion process, the swine wastewater is used as a liquid biofertilizer in conventional pastures or in silvo-pastures. However, adverse impacts have been attributed to swine wastewater overdoses, such as groundwater contamination and increased greenhouse gas emissions. The objective of this work was to evaluate soil-biological activity by measuring carbon dioxide flux in three pasture conditions (conventional, silvopastures with single lines of Eucalyptus sp., and silvopastures with double lines of Eucalyptus sp.) after the application of biofertilizer in five dosages (0, 200, 400, 600 and 800 m3ha-1ano-1). In addition to total organic carbon (TOC), fulvic acid (FA), humic acid (HA), humin and cation exchange capacity (CEC) were also measured. As expected, CO2 emission or basal respiration of the soil showed greater activity in the first days after application, especially when larger dosages were used. No consistent pattern was observed from measurements in pastures without addition of biofertilizer, as well as in the silvopastoral system with double line of Eucalyptus sp. (0 and 200 m3ha-1ano-1). For other time series, a significant correlation was found between CO2 emission and time after biofertilizer was used (days), given that Carbon dioxide emission reduces exponentially, day after day. We also evidenced that increasing biofertilizer dosages promotes increasing carbon concentration in a constant linear relation The same pattern was evidenced in fractioned organic matter (FA, HA and humin). Our results corroborate to assumption that the prediction of overdose is feasible, as well as the anticipation of the response of specific attributes of the soil, such as CEC. However, in this experiment even the highest doses showed positive responses to fertility, increasing soil CEC.